2022
DOI: 10.1039/d2ta02576k
|View full text |Cite
|
Sign up to set email alerts
|

Anti-freezing, conductive and shape memory ionic glycerol-hydrogels with synchronous sensing and actuating properties for soft robotics

Abstract: Soft devices based on hydrogels are attracting increasing attention, but it is still a challenge to prepare hydrogels with remarkable strength, strain sensing sensitivity, anti-freezing properties, synchronously sensing and actuating...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…[11] Due to the potential detrimental effect of freezing water on the physical and mechanical behaviors of tough hydrogels, attempts have been made to make antifreeze physically crosslinked hydrogels by taking advantage of supramolecular interactions [12] or reducing the freezing point of a hydrogel by adding glycerol and/or NaCl to the hydrogel. [13][14][15][16][17] Other studies in this area include fabrication of ionic anti-freezing stretchable hydrogel based on poly(vinyl alcohol)/urea, [18] stretchable and anti-freezing hybrid DN organohydrogels, [19] biomimetic organohydrogel electrolytes, [20] and design of super-elastic mineral hydrogel based on dynamic physical crosslinking between hydrated calcium ion clusters and amide groups of polyacrylamide network. [21] It should be noted that some of the strategies that were mentioned above to improve the behavior of hydrogels for experiencing high temperature variations, such as changing the freezing point of hydrogels, may affect their other functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Due to the potential detrimental effect of freezing water on the physical and mechanical behaviors of tough hydrogels, attempts have been made to make antifreeze physically crosslinked hydrogels by taking advantage of supramolecular interactions [12] or reducing the freezing point of a hydrogel by adding glycerol and/or NaCl to the hydrogel. [13][14][15][16][17] Other studies in this area include fabrication of ionic anti-freezing stretchable hydrogel based on poly(vinyl alcohol)/urea, [18] stretchable and anti-freezing hybrid DN organohydrogels, [19] biomimetic organohydrogel electrolytes, [20] and design of super-elastic mineral hydrogel based on dynamic physical crosslinking between hydrated calcium ion clusters and amide groups of polyacrylamide network. [21] It should be noted that some of the strategies that were mentioned above to improve the behavior of hydrogels for experiencing high temperature variations, such as changing the freezing point of hydrogels, may affect their other functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic strain sensing has been explored for wearable devices, 33,64 soft robotics, 22,49 and cardiac output monitoring. 12 Recent work has demonstrated that ionically conductive gels can also be designed to accurately monitor body temperature through wearable devices.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 To replace conventional thin-film metal conductors typically operated under non-alternating DC voltages, there has been a targeted effort in increasing the conductivity of soft hydrogels. This has been pursued through two primary means: (i) using conductive polymers such as PEDOT:PSS to form the hydrogel matrix; 19,45,46 and (ii) utilizing conductive fillers such as metallic nano-and micro-particles (Au, Ag, Pt), carbon-based materials, ionic liquids, [47][48][49] and MXenes within polymer matrices. [50][51][52][53][54] There has been considerable success in applying these materials in sensing both mechanical deformation and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable flexible sensors, which can be changed into different shapes and attached onto diverse convex surfaces, have been widely investigated in skin sensors, ,, retractable displays, , human tissues, soft robots, and other fields. To construct flexible electronic wearable strain sensors, a general route is to incorporate conductive elements within elastic materials to produce electrical impulses. ,, Among various elastomer materials, hydrogels, as three-dimensional (3D) structures composed of chemical or physical polymers and water, have become the focus of scientists’ attention for their excellent tensile properties and biocompatibility. ,,, …”
Section: Introductionmentioning
confidence: 99%